2015
DOI: 10.1016/j.respol.2014.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Foreign multinationals and domestic innovation: Intra-industry effects and firm heterogeneity

Abstract: This paper looks at foreign Multinational Enterprises (MNEs) investing in the UK and at their impact on the innovation performance of domestic firms active in their same sector. By employing data on Foreign Direct Investments matched with firm-level information the paper develops a direct measure of capital inflows at a three-digit industry level. In order to capture innovation in both manufacturing and services the paper relies on a broader proxy for firm innovativeness based on the Community Innovation Surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 93 publications
(62 citation statements)
references
References 84 publications
1
55
0
3
Order By: Relevance
“…Since technological development tends to be cumulative in nature and characterized by elements that are bounded in specific places, it is suggested that MNEs establish networks for innovation across locations by tapping into regional profiles of specialization and strengthening local technological competencies, thus feeding a regional hierarchy of centers across and within national boundaries (Cantwell and Iammarino 2003). The interactions between regional knowledge bases and MNEs technological strategies are investigated in terms of knowledge spillovers and externalities, particularly in the European (e.g., Cantwell and Piscitello 2005;Ascani and Gagliardi 2014;Crescenzi, Gagliardi, and Iammarino 2015) and the US context (e.g.,…”
Section: Mnes Location Strategies: Host Economy Advantages and Institmentioning
confidence: 99%
“…Since technological development tends to be cumulative in nature and characterized by elements that are bounded in specific places, it is suggested that MNEs establish networks for innovation across locations by tapping into regional profiles of specialization and strengthening local technological competencies, thus feeding a regional hierarchy of centers across and within national boundaries (Cantwell and Iammarino 2003). The interactions between regional knowledge bases and MNEs technological strategies are investigated in terms of knowledge spillovers and externalities, particularly in the European (e.g., Cantwell and Piscitello 2005;Ascani and Gagliardi 2014;Crescenzi, Gagliardi, and Iammarino 2015) and the US context (e.g.,…”
Section: Mnes Location Strategies: Host Economy Advantages and Institmentioning
confidence: 99%
“…However, compensation effects of higher valueadded productions and job creation in the home economy are also likely to emerge, particularly in the case of FDI towards regions and countries with a relatively lower level of development (e.g., Barba Navaretti, Castellani, & Disdier, 2010;Castellani & Pieri, 2016;Driffield, Love, & Taylor, 2009;Gagliardi, Iammarino, & RodriguezPose, 2015;Grossman & Rossi-Hansberg, 2006). Positive effects may be strengthened over time thanks to efficiency gains linked to the geographical rationalization of production along the value chain, and to the dynamic benefits stemming from tapping into new sources of innovation and technical knowledge elsewhere (Cantwell & Iammarino, 2003;Castellani & Pieri, 2013;Crescenzi, Gagliardi, & Iammarino, 2015).…”
mentioning
confidence: 99%
“…In consideration of stability, the efficiency, sales, capital intensity, profit and political connections of firms are, as control variables, included in the equation (21). The control variables are chosen by reference to Howitt et al (2005) and Crescenzi et al (2015).…”
Section: Methodsmentioning
confidence: 99%